Reinforced concrete building design project and project based learning / Muhammad Najmi Najhan Mohd Azhan - Mohd Azhan, Muhammad Najmi Najhan (2023)
From the structural plan, we chose one for each structures in the building. Before we started calculating, the permanent load, Gk and variable load, Qk was determined. Then, we choose the slab. The slab I designed was two-way slab. For the continuous beam, I chose the beam that was attached to the slab I chose. The column I chose also attached to my beam and the column was a short column. For the pad footing, it was under the column I chose and by using the SI report that we got we managed to design the pad footing. For staircase, we determine the strength of the concrete we will use.